1995
DOI: 10.1677/joe.0.1460183
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon-like peptide-1 binding to rat hepatic membranes

Abstract: We have found [125I]glucagon-like peptide (GLP)-1(7-36)amide specific binding activity in rat liver and isolated hepatocyte plasma membranes, with an M(r) of approximately 63,000, estimated by cross-linking and SDS-PAGE. The specific binding was time- and membrane protein concentration-dependent, and equally displaced by unlabelled GLP-1(7-36)amide and by GLP-1(1-36)amide, achieving its ID50 at 3 x 10(-9) M of the peptides. GLP-1(7-36)amide did not modify the basal or the glucagon (10(-8) M)-stimulated adenyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
40
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(46 citation statements)
references
References 28 publications
6
40
0
Order By: Relevance
“…The liver has repeatedly been reported to be a target for GLP-1, although initial careful studies indicated that hepatocytes did not express GLP-1 receptor (17). Thus GLP-1 has been reported to bind to rat hepatic membranes but without influencing adenylate cyclase activity, as expected from the classical GLP-1 receptor (308). Rather, inositol phosphoglycans were thought to act as mediators (291).…”
Section: Whole Body Effects Peripheral Effects and Effects On Inmentioning
confidence: 99%
“…The liver has repeatedly been reported to be a target for GLP-1, although initial careful studies indicated that hepatocytes did not express GLP-1 receptor (17). Thus GLP-1 has been reported to bind to rat hepatic membranes but without influencing adenylate cyclase activity, as expected from the classical GLP-1 receptor (308). Rather, inositol phosphoglycans were thought to act as mediators (291).…”
Section: Whole Body Effects Peripheral Effects and Effects On Inmentioning
confidence: 99%
“…However, it is known that GLP-1 specifically binds to the plasma membranes of major extrapancreatic tissues participating in glucose homeostasis and lipid metabolism, indicating the presence of receptors which, in liver and muscle at least, seem to be structurally or functionally different (8)(9)(10)(11) from that in the pancreas (12).…”
Section: Introductionmentioning
confidence: 99%
“…[Diabetologia (2002[Diabetologia ( ) 45:1410[Diabetologia ( -1415 Keywords GLP-1, exendin-4, insulin action, glucose production, cortisol secretion. [11,12] and the liver [13]. GLP-1 (7-36) can increase glucose uptake in each of these tissues with its effects being additive to those of insulin [12,14,15,16].…”
Section: Introductionmentioning
confidence: 99%